2016
DOI: 10.1159/000444590
|View full text |Cite
|
Sign up to set email alerts
|

Children with Dry Skin and Atopic Predisposition: Outcome Measurement with Validated Scores for Atopic Dermatitis

Abstract: Background: Dry skin is a common skin condition in childhood. Few studies exist investigating the influence of daily skin care on dry skin in infants at risk of developing atopic dermatitis (AD). We aimed to assess the effect of skin care on dry skin in this special cohort using validated scores for AD and analysis of skin microtopography. Methods: 43 children were randomized to group 1 (G1) and group 2 (G2) and 22 infants to group 3 (G3). During 16 weeks, G1 and G3 applied daily a plant-based emollient and G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…There is evidence that topical corticosteroids may further damage the skin barrier alongside of the beneficial suppression of inflammation in AD patients, and increases in TEWL in skin of patients have been observed under treatment with topical corticosteroids [25, 26]. Additionally, there is accumulating evidence that daily use of emollients may improve both TEWL and stratum corneum hydration measurements [19, 27], suggesting that topical application in our trial may have influenced the TEWL outcome in both groups. Indeed, the measurement of skin hydration in addition to TEWL and their correlation to AD severity scores [27] would have added valuable additional information.…”
Section: Discussion/conclusionmentioning
confidence: 88%
See 1 more Smart Citation
“…There is evidence that topical corticosteroids may further damage the skin barrier alongside of the beneficial suppression of inflammation in AD patients, and increases in TEWL in skin of patients have been observed under treatment with topical corticosteroids [25, 26]. Additionally, there is accumulating evidence that daily use of emollients may improve both TEWL and stratum corneum hydration measurements [19, 27], suggesting that topical application in our trial may have influenced the TEWL outcome in both groups. Indeed, the measurement of skin hydration in addition to TEWL and their correlation to AD severity scores [27] would have added valuable additional information.…”
Section: Discussion/conclusionmentioning
confidence: 88%
“…Interestingly, while symptoms decreased over time in both groups, possibly highlighting the natural improvement of the disease symptoms, the usage of topical fluticasone did not change over time, suggesting sustained need for topical treatment in this population. Other recent studies have shown the usefulness of different scoring systems such as the Patient-Oriented SCORAD (PO-SCORAD) to measure response to treatment [19]; such readout should be considered as an outcome in future trails.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…can dramatically impair quality of life of many patients. On the other hand, appropriate moisturization and emollient treatment of the skin can alleviate symptoms, and in some cases, they are even able to prevent the onset of AD (Hoppe et al, 2015;Sawatzky et al, 2016;Sugiura et al, 2014). Although inappropriate epidermal ceramide production is thought to be the most important player in these processes, a growing body of evidence now supports the concept that dysregulation of SG functions and the subsequent alterations in the SLP are also fundamental.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the previous studies, a control group without topical treatment was not feasible in our study population due to the patients’ dry skin and high risk of developing AD ( Williams et al, 2012 ). Moreover, a sufficient amount of data on untreated healthy infantile skin barrier parameters under comparable conditions is available ( Gao and Simpson, 2014 , Ludriksone et al, 2014 , Sawatzky et al, 2016 ). Therefore, two formulations on different body areas were chosen to identify their effect on the skin barrier function in this specific dermatological risk group.…”
Section: Discussionmentioning
confidence: 99%